2007
DOI: 10.1016/j.virol.2006.09.048
|View full text |Cite
|
Sign up to set email alerts
|

Complex determinants within the Moloney murine leukemia virus capsid modulate susceptibility of the virus to Fv1 and Ref1-mediated restriction

Abstract: Two of the most well-known genetic mechanisms in mammalian cells which control the susceptibility of cells to productive infection by retroviruses and lentiviruses rely on the cellular Fv1 and Ref1 restriction factors, which act, after viral entry, to prevent productive infection through their interactions with viral capsid (CA) sequences. While previous studies of Fv1 restriction involving N- and B-tropic murine leukemia viruses (MLVs) had demonstrated that the identity of a single amino acid residue at CA110… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 33 publications
1
24
0
Order By: Relevance
“…4A and Fig. S4), including the β1/β2 hairpin, L5/6, and L4/5 regions in HIV CA and the corresponding sites on MLV CA (30,33,(45)(46)(47)(48)(49)(50). Specifically, TRIM5α V1 may interact with CA β1/β2 at the center of the CA hexamer, as swapping the V1 region of rhTRIM5α and huTRIM5α resulted in a change of the restriction specificity toward MLV CA with mutations in the β1/β2 region (30).…”
Section: Discussionmentioning
confidence: 99%
“…4A and Fig. S4), including the β1/β2 hairpin, L5/6, and L4/5 regions in HIV CA and the corresponding sites on MLV CA (30,33,(45)(46)(47)(48)(49)(50). Specifically, TRIM5α V1 may interact with CA β1/β2 at the center of the CA hexamer, as swapping the V1 region of rhTRIM5α and huTRIM5α resulted in a change of the restriction specificity toward MLV CA with mutations in the β1/β2 region (30).…”
Section: Discussionmentioning
confidence: 99%
“…Infection assays utilized single-round viruses carrying either green fluorescent protein (GFP) or luciferase reporter genes. GFP-based constructs included equine infectious anemia virus (EIAV) (56,57), HIV-1 (31), Rous sarcoma virus (RSV) (12) (Addgene plasmid 13878; obtained from Constance Cepko via Addgene, Cambridge, MA), FIV (36,46), MLV (58,68), Mason-Pfizer monkey virus (MPMV) (55), HIV-2 strain ROD (HIV-2 ROD ), and simian immunodeficiency viruses from Macaca mulatta (SIV MAC ), Chlorocebus sabaeus (SIV AGM Sab), and Chlorocebus tantalus (SIV AGM Tan) (82). Luciferasebased viruses included MLV/HIV-1 LAI chimeras (75,76) and HIV-1 NL4-3 -derived D64N/D116N (N/N) IN active site and Vpr and/or DNA flap mutants of pNLX.Luc (45,47).…”
Section: Methodsmentioning
confidence: 99%
“…The three resistance alleles of Fv1 target specific residues in the virus capsid. Capsid amino acid 110 distinguishes N-and B-tropic viruses (25), but various substitutions in amino acid positions 82 to 117 of the CA N-terminal domain can generate NR-or NB-tropic viruses (12,20,27,39,44).…”
Section: Resultsmentioning
confidence: 99%
“…CA110 is the target for Fv1 n (E110) and Fv1 b (R110) restriction (25), and MLVs bearing R110, A110, and H117 are restricted by human TRIM5␣ (49). Studies on naturally occurring or mutated MLVs with altered tropism have identified at least eight additional positions within the CA82-214 segment that can alter sensitivity to Fv1 or TRIM5␣, and these tropism-determining residues can be masked or modulated when combined (12,20,27,39,44). A similar ability to target multiple capsid residues or combinations of residues may also explain why the 2-amino-acid Minr target identified in AKV MLV (R110 L117) was not present in three of the six restricted viruses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation